Res maritimae : Cyprus and the Eastern Mediterranean from prehistory to late antiquity : proceedings of the second international symposium “cities on the sea” : Nicosia, Cyprus, October 18-22, 1994 (Atlanta, Georgia)
viii, 372 s.